2005
DOI: 10.1063/1.1849817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain size on the electrical properties of (Ba,Ca)(Zr,Ti)O3 relaxor ferroelectric ceramics

Abstract: ͑Ba 0.90 Ca 0.10 ͒͑Zr 0.25 Ti 0.75 ͒O 3 (BCZT) relaxor ferroelectric ceramics with grain sizes of 0.85, 2.5, 15, and 30 m were prepared from powders synthesized using a sol-gel process. The effects of grain size and dc field on the dielectric properties and tunabilities of BCZT ceramics were investigated. As the grain size decreased, the maximum dielectric constant decreased and the transition temperature increased. The BCZT ceramics with various grain sizes showed a typical relaxor ferroelectric behavior. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(39 citation statements)
references
References 23 publications
7
32
0
Order By: Relevance
“…In addition, a parameter ∆T 1 (∆T 1 = T m − T VF ) is also listed in table Table III, to compare the relative freezing temperatures for all samples. 80 For pure and glass added BNT-BT-ST ceramics, ∆T 1 also increases. It suggests that the relaxor behaviors in these systems are analogous to that of a dipolar glass with polarization fluctuations above a freezing temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a parameter ∆T 1 (∆T 1 = T m − T VF ) is also listed in table Table III, to compare the relative freezing temperatures for all samples. 80 For pure and glass added BNT-BT-ST ceramics, ∆T 1 also increases. It suggests that the relaxor behaviors in these systems are analogous to that of a dipolar glass with polarization fluctuations above a freezing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The relaxor behavior can be induced by several means such as microscopic composition fluctuation, the merging of micropolar regions into macropolar regions, or a coupling of order parameter and local disorder mode through the local strain. 78,80 Additionally, it was observed that temperature also affects domain growth and domain wall motion in ferroelectric ceramics. It is reported in literature that as the temperature increases coercive field, P s and P r decreases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, such effect on the relaxor behaviour is mainly reported in lead based compounds. Regarding the lead free nanostructured ceramics, this was mainly discussed in the BCTZ case [28][29][30][31]. Such lack in the materials property understanding must be filled out to develop the nanosized components required for a higher degree of integration in electronic devices.…”
Section: Introductionmentioning
confidence: 98%